Effect of Bone Marrow–Derived Mononuclear Cell Treatment, Early or Late After Acute Myocardial Infarction: Twelve Months CMR and Long-Term Clinical Results. Issue 3 (22nd July 2016) - Sürder, Daniel; Manka, Robert; Moccetti, Tiziano; Lo Cicero, Viviana; Emmert, Maximilian Y.; Klersy, Catherine; Soncin, Sabrina; Turchetto, Lucia; Radrizzani, Marina; Zuber, Michel; Windecker, Stephan; Moschovitis, Aris; et al.
Abstract : Rationale: : Intracoronary delivery of autologous bone marrow–derived mononuclear cells (BM-MNC) may improve remodeling of the left ventricle (LV) after acute myocardial infarction (AMI). Objective: : To demonstrate long-term efficacy of BM-MNC treatment after AMI. Methods and Results: : In a multicenter study, we randomized 200 patients with large AMI in a 1:1:1 pattern into an open-labeled control and 2 BM-MNC treatment groups. In the BM-MNC groups, cells were either administered 5 to 7 days (early) or 3 to 4 weeks (late) after AMI. Cardiac magnetic resonance imaging was performed at baseline and after 12 months. The current analysis investigates the change from baseline to 12 months in global LV ejection fraction, LV volumes, scar size, and N-terminal pro-brain natriuretic peptide values comparing the 2 treatment groups with control in a linear regression model. Besides the complete case analysis, multiple imputation analysis was performed to address for missing data. Furthermore, the long-term clinical event rate was computed. The absolute change in LV ejection fraction from baseline to 12 months was −1.9±9.8% for control (mean±SD), −0.9±10.5% for the early treatment group, and −0.7±10.1% for the late treatment group. The difference between the groups was not significant, both for complete case analysis and multiple imputation analysis. A combined clinical end point occurred equally in all the groups. Overall, 1-year mortality was low (2.25%). Conclusions: : Among patients with AMI and LV dysfunction, treatment with BM-MNC either 5 to 7 days or 3 to 4 weeks after AMI did not improve LV function at 12 months, compared with control. The results are limited by an important drop out rate. Clinical Trial Registration Information: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT00355186. Abstract : Supplemental Digital Content is available in the text.